ANALYSIS OF THE EFFECT OF MOTIVATION, AND LEADERSHIP STYLE ON EMPLOYEES' WORK SPIRIT AT CV. THE FIVE MAIN OF BANYUWANGI - Nur Holis, Muhammad; Dwi Alvianu Alif, Diki (CV. Radja Publika, 2022)
This research aims to determine the effect of the variables to be studied, namely motivation and leadership style whether they have a positive influence on work morale. The sample in this study was determined by a census approach with all employees in the company being the research sample, namely 44 people at CV. Five Main Banyuwangi. This study uses a questionnaire method, and data processing using multiple linear regression analysis. Data processing in this study used SPSS 24. Furthermore, the data obtained from filling out questionnaires, study documentation, and interviews with respondents were tested using multiple linear regression analysis. The results showed that there was a significant combination and a partial effect, the independent variables namely Motivation, and Leadership Style on the production variable, namely Employee Morale at CV. Five Main Banyuwangi.